Lifestyle interventions for blood pressure reduction and hypertension prevention in adolescents: A systematic review - Siregar, Hasbunsyah; Permatasari, Henny; Nursasi, Astuti Yuni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hypertension in adolescents is an emerging public health concern, often linked to poor lifestyle habits formed early in life. Lifestyle interventions have been recommended as first-line, non-pharmacological strategies for blood pressure control and hypertension prevention. Purpose: To evaluate the effectiveness of lifestyle interventions in reducing blood pressure and preventing hypertension among adolescents. Method: A systematic literature review was conducted on June 30, 2025, using the PICO framework. Databases searched included PubMed, Sage Journals, ScienceDirect, and Google Scholar. Keywords included Lifestyle Interventions, Hypertension, and Adolescents. Inclusion criteria were original studies (RCTs, cohort, quasi-experimental) focusing on adolescents with lifestyle-based interventions. Articles in English or Indonesian were included if full-text was available and outcomes reported changes in blood pressure, BMI, or lifestyle practices. Results: The reviewed studies consistently demonstrated that lifestyle interventions such as increased physical activity, dietary modification, and health education effectively reduced both systolic and diastolic blood pressure. Several interventions also resulted in improved BMI, physical fitness, and healthier lifestyle practices. Multicomponent and early interventions, particularly those implemented in schools and supported by family or community involvement, showed the most promising results. However, some adolescents with severe obesity or resistant hypertension may require complementary medical treatment. Conclusion: Lifestyle interventions are effective, scalable, and evidence-based strategies for lowering blood pressure and preventing hypertension in adolescents. These findings support their integration into public health initiatives aimed at reducing long-term cardiovascular risk from an early age.